Impact of Baijiu geographical indication product certification on consumer purchasing behavior - WANG Kai, WU Mengli, TONG Jun (Zhongguo niangzao)
To evaluate the impact of Baijiu geographical indication certification on consumer purchasing decisions, its spatial distribution characteristics and regional differences characteristics in China's four major regions (East, Central, West, and Northeast) was explored by geographical concentration index method. "Guizhou Moutai" (well-known domestic Baijiu brand) was selected as a case study subject, with consumer purchasing behavior as the dependent variable, and the functional value, emotional value, economic value, and safety value of product as independent variables, theoretical model was constructed based on consumer purchasing behavior theory. The results showed that the distribution of China's Baijiu geographical indication products was significantly uneven nationwide, with a higher concentration within the four major regions. Among them, the Northeast region had the highest geographical concentration index (57.960). Taking "Guizhou Moutai" as an example, the perceived value of Baijiu geographical indication products had a significant positive impact on consumer purchasing behavior. In terms of impact degree, the order of impact was economic value (0.349)>functional value (0.259)>safety value (0.179)>emotional value (0.169).